Peran Industri Rumah Tangga Dalam Pemberdayaan Ekonomi Keluarga dan Masyarakat (Studi Pada Industri Rumah Tangga Getas dan Kemplang di Desa Kuarau, Bangka Tengah) - Luna Febriani; Siti Saleha (Jurnal Community, 2021)
Community empowerment is an important part of the development process and improving community welfare. Industri Rumah Tangga and Micro, Small and Medium Enterprises (UMKM) are part of the empowerment process that can strengthen the family economic and community economy resilience. Community empowerment through a Industri Rumah Tangga or household business is also carried out in community of Kurau Village, Koba District, Bangka Belitung Islands Province. Industri Rumah Tangga of Kemplang and Getas were initiated by this community became commodities that strengthened the family and community economies. This study aims to explore the role of the Industri Rumah Tangga in the economy and the empowerment process of Getas and Kempalng’s Industri Rumah Tangga in Kurau Village. The research method used in this research is descriptive qualitative, with the theory of community empowerment as a theory to analalize the data. The results showed that Getas and Kemplang’s Industri Rumah Tangga in Kurau has a significant role in strengthening the family and community economy, this can be seen from the level of economic income of the Kurau Village community after this business. Apart from that, the background of its establishment cannot be separated from the increasingly urgent economic demands, so that this business can become a support for society in the economic field. For community empowerment, this business is a type of bottom up empowerment, which is initiated by the community, starting from the production process to the distribution process to distributors both in Kurau Village and outside the village.